Acute kidney injury in a tropical country: a cohort study of 253 patients in an infectious diseases intensive care unit - Daher,Elizabeth De Fransceco (2014)
Introduction: Acute kidney injury (AKI) is a frequent and potentially fatal complication in infectious diseases. The aim of this study was to investigate the clinical aspects of AKI associated with infectious diseases and the factors associated with mortality. Methods: This retrospective study was conducted in patients with AKI who were admitted to the intensive care unit (ICU) of a tertiary infectious diseases hospital from January 2003 to January 2012. The major underlying diseases and clinical and laboratory findings were evaluated. Results: A total of 253 cases were included. The mean age was 46±16 years, and 72% of the patients were male. The main diseases were human immunodeficiency virus (HIV) infection, HIV/acquired immunodeficiency syndrome (AIDS) (30%), tuberculosis (12%), leptospirosis (11%) and dengue (4%). Dialysis was performed in 70 cases (27.6%). The patients were classified as risk (4.4%), injury (63.6%) or failure (32%). The time between AKI diagnosis and dialysis was 3.6±4.7 days. Oliguria was observed in 112 cases (45.7%). The Acute Physiology and Chronic Health Evaluation (APACHE) II scores were higher in patients with HIV/AIDS (57±20, p-value=0.01) and dengue (68±11, p-value=0.01). Death occurred in 159 cases (62.8%). Mortality was higher in patients with HIV/AIDS (76.6%, p-value=0.02). A multivariate analysis identified the following independent risk factors for death: oliguria, metabolic acidosis, sepsis, hypovolemia, the need for vasoactive drugs, the need for mechanical ventilation and the APACHE II score. Conclusions: AKI is a common complication in infectious diseases, with high mortality. Mortality was higher in patients with HIV/AIDS, most likely due to the severity of immunosuppression and opportunistic diseases.